Analisis Pengaruh Nilai Parameter Proses Pemesinan Milling Terhadap Kekasaran Permukaan Almunium 7075 - Mahendra, Anan; Yudo, Eko; Kurniawan, Zaldy (Jurnal Inovasi Teknologi Terapan, 2023)
Miiling machining is one of the machining processes that are widely used for the manufacture of a component of goods with a milling machining process, the time required to make components should be as minimal as possible so that high production capacity can be achieved. The maximum cutting process parameter will result in a high rate of material feeding, so it can also result in the appropriate surface roughness (Ra) desired. The purpose of this study is to obtain the lowest surface roughness value produced by the process from CNC milling with the parameters used and to determine the level of roughness of the aluminum surface using the depth of cut, cutting speed, and rotation speed. The method used is the Taguchi method with three parameters, namely spindle rotation (Rpm), Feeding Depth, Feeding Speed taken from this study the results of a tool data called roungnes tester obtained and directly retrieving the most optimal value data of 0.239 Ra which has been averaged. Then in the percentage up to these three factors that have been done.from the results have been obtained have a small prenstasi of 30% and obtained a response value of less than 1%. This taguchi method is to improve product quality and process in about the same time. The results of this optimization are used to try the operator's consideration when determining the combination to get the optimal value possible.